Pharmacokinetic Interactions between the Hormonal Emergency Contraception, Levonorgestrel (Plan B), and Efavirenz. (28th February 2012) - Carten, Monica L.; Kiser, Jennifer J.; Kwara, Awewura; Mawhinney, Samantha; Cu-Uvin, Susan
Abstract : Objectives . Compare the Plan B levonorgestrel (LNG) area under the concentration- time curve (AUC12 ) prior to and with efavirenz (EFV). Design . Prospective, open-label, single-arm, equivalence study. Methods . Healthy HIV-negative subjects underwent 12 hr intensive pharmacokinetic (PK) sampling following single dose LNG alone and after 14 days of EFV. Geometric means, Geometric Mean Ratios, and 90% confidence intervals (CI) are reported for PK Parameters. T -tests were utilized. Clinical parameters and liver function tests (LFTs) were assessed. Results . 24 women enrolled and 21 completed the study. With EFV, LNG AUC12 was reduced 56% (95% CI: 49%, 62%) from 42.9 to 17.8 ng*hr/mL, and maximum concentration (C max ⁡ ) was reduced 41% (95% CI: 33%, 50%) from 8.4 to 4.6 ng/mL. LNG was well tolerated with no grade 3 or 4 treatment-related toxicities. Conclusions . EFV significantly reduced LNG exposures. Higher LNG doses may be required with EFV. These results reinforce the importance of effective contraception in women taking EFV.